Detection of broiler feeds contamination with Aflatoxins using rapid immunochromatographic test strips - B.S.S. Khalaf; N.M.A. Younis; N.T.M. Sideeq; Y.S.M. Sultan; A.M. Shareef (Iraqi Journal of Veterinary Sciences, 2015)
Twenty pellet broiler feed samples (started or finished) were collected through October to December 2013, from 12 broiler flocks and 8 feed mills in Nineveh governorate, for the detection of Aflatoxins residue using total Aflatoxins rapid test strips kit. Results show that 3 (15%) of the feed samples were positive while 17 feed samples (85%) were negative to residual Aflatoxin.